Laser-engineered rattan evaporators for scalable and sustainable solar desalination - Xu, Haocheng; Liu, Yingpeng; Woon, Pei Qi; Chen, Meiling; Xu, Xinwu; Li, Bofan (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Scalable and sustainable solar-driven interfacial evaporators are vital to addressing global freshwater scarcity and sustainability challenges. However, the applicability of biomass-based evaporators is often limited by costly and complex fabrication processes. Here, we report a high-performance rattan-based solar evaporator fabricated via a one-step laser-induced carbonization process. This direct approach creates a multi-dimensional hierarchical light-harvesting layer with a pronounced 3D periodic protrusion array, achieving a high solar absorptance of 88.32 %. This structure significantly enhances evaporation by increasing the effective evaporation area, promoting omnidirectional vapor escape and inducing dual Marangoni flows that facilitate liquid circulation and salt backflow. The evaporator achieves a high energy conversion efficiency of 95.32 % and water evaporation rate of 1.80 kg·m−2·h−1 in simulated seawater, with a significant reduction in evaporation latent heat to 1.62 MJ·kg−1, outperforming many previously reported carbon- or bio-based evaporators. Integrated into a closed-loop desalination-cultivation system, the generated freshwater supports wheat cultivation over an area 3 times larger than the evaporation surface, yielding plant growth comparable to tap water irrigation. Life cycle assessment reveals the rattan-based evaporator produces over two orders of magnitude lower CO2-equivalent emissions and substantially reduces overall environmental impacts compared to conventional solar evaporators. This work demonstrates a scalable and environmentally friendly strategy to transform natural biomass into high-performance sustainable solar evaporators, advancing decentralized water-food solutions under resource-constrained conditions. [Display omitted] •CO2 laser-carbonized rattan enables efficient, scalable solar desalination.•Natural rattan microchannels enable fast water transport and salt backflow.•Multi-dimensional light harvest enhanced efficiency without extra energy input.•3D periodic protrusion array induces dual-Marangoni flow sustaining salt-rejection.•Freshwater generation for low-carbon closed-loop desalination-cultivation system.